2020
DOI: 10.3390/ijerph17186632
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Body Size Perception and Body Image (Dis)Satisfaction in the Elderly: Results of the ELSA-Brasil Study

Abstract: The study aimed to assess the association between body image perception and (dis)satisfaction and sociodemographic and behavioral factors in the elderly, using multinomial logistic regression. Data were analyzed for 1686 women and 1499 men participating in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Men with less schooling and women with lower per capita income showed higher odds of underestimating their body size. Former smokers of both sexes showed higher odds of overestimating their body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
2
0
4
Order By: Relevance
“…Quanto à escolaridade, as mulheres que distorcem para mais peso têm maior escolaridade e as que distorcem para menos peso são menos escolarizadas. A literatura mostra que, entre as participantes do ELSA-Brasil, as chances de subestimar o tamanho corporal aumentaram três vezes em relação à menor escolaridade, enquanto a escolaridade primária e a baixa renda per capita diminuíram em 30% as chances de superestimar ligeiramente o tamanho corporal 37 . Ou seja, a escolaridade demonstra relação importante com a percepção da imagem corporal entre as mulheres, de forma que, quanto menor a escolaridade, mais elas subestimam o próprio tamanho.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Quanto à escolaridade, as mulheres que distorcem para mais peso têm maior escolaridade e as que distorcem para menos peso são menos escolarizadas. A literatura mostra que, entre as participantes do ELSA-Brasil, as chances de subestimar o tamanho corporal aumentaram três vezes em relação à menor escolaridade, enquanto a escolaridade primária e a baixa renda per capita diminuíram em 30% as chances de superestimar ligeiramente o tamanho corporal 37 . Ou seja, a escolaridade demonstra relação importante com a percepção da imagem corporal entre as mulheres, de forma que, quanto menor a escolaridade, mais elas subestimam o próprio tamanho.…”
Section: Discussionunclassified
“…Em contrapartida, Marques et al 40 demonstraram que os resultados referentes ao nível educacional marcam maior insatisfação corporal entre as mulheres mais escolarizadas. Fonseca et al 37 , por sua vez, revelaram que tanto homens quanto mulheres com menor escolaridade apresentaram maiores chances de insatisfação devido ao excesso de peso. Essas diferentes perspectivas mostram as possibilidades de interação da variável escolaridade a partir da população estudada.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Despite the above-mentioned limitations, our study was the first to show the contribution by birth weight and sociodemographic variables to perceived weight changes over time. We stratified the analyses by sex considering that perceived body image is different for men and women, with men tending to underestimate and not distort their body size, while women tend to overestimate their body size [ 32 ]. Furthermore, the satisfactory stability of the body sizes chosen by the participants to indicate previous body sizes strengthens the results obtained in the trajectory analysis (Additional file 1 ) and contributes to expanding the assessment of the psychometric quality of the silhouette scales used.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study with participants in ELSA-Brasil found that body image differed between men and women. Men tended to underestimate and not distort their body size, while women tended to overestimate their body size [ 32 ]. The way individuals perceive their bodies can impact self-perceived body shape trajectories, so we stratified the analyses by sex.…”
Section: Methodsmentioning
confidence: 99%